2018
DOI: 10.4236/ojd.2018.72002
|View full text |Cite
|
Sign up to set email alerts
|

Armed Conflict and Depression among Heads of Households in Dogonahawa, North-Central Nigeria: Prevalence and Correlates

Abstract: Background and Aim: Research has shown that 30%-70% of people who have lived in war zones suffer from symptoms of depression, with exceptionally high rates documented among heads of households. Thus, this study aims to determine the prevalence and correlates of depression among victims of armed-conflict in Dogonahawa, North-Central Nigeria. Methods: A multistage sampling of households was employed to select 270 respondents aged ≥ 18 years. A face-to-face interview was conducted using the Revised Beck Depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
(20 reference statements)
0
7
1
Order By: Relevance
“…While comparing, the result of this study was lower than other studies conducted in North-Eastern Nigeria 63.7% [ 16 ], and Siri Lanka 68% [ 27 ]. The possible justification could be, variation in the study population, this study includes Woldia town residents aged 18 and above, but in a study conducted in, North-Eastern Nigeria and Siri Lanka participants were only 15 to 35 years, school-aged, children and adolescents respectively.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…While comparing, the result of this study was lower than other studies conducted in North-Eastern Nigeria 63.7% [ 16 ], and Siri Lanka 68% [ 27 ]. The possible justification could be, variation in the study population, this study includes Woldia town residents aged 18 and above, but in a study conducted in, North-Eastern Nigeria and Siri Lanka participants were only 15 to 35 years, school-aged, children and adolescents respectively.…”
Section: Discussioncontrasting
confidence: 90%
“…In another study in Uganda, seven years after the conflict in three districts, (The Wayo-Nero Study) revealed, respondents with previous negative life events (familial, physical and psychological events) had prevalence of PTSD found to be 11.8% [ 15 ]. A study among victims of Boko haram terrorism in north-eastern Nigeria, more than 63% of the respondents were diagnosed with PTSD [ 16 ]. Following a three year civil war in Northern Nigeria a cross sectional study using a multistage sampling technique was study in northern Nigeria among 200 older adults, confirms 59% for full PTSD [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence of mental disorders could be even higher in regions with more intense conflicts and casualties. For example, the prevalence of depression was 38.5% among a random sample of households in Dogo Nahawa, North-Central Nigeria, where citizens were undergoing frequent and intense violent conflicts and massacre in the past decades ( Taru et al, 2018 ). Prevalences of depression and anxiety were estimated to be 41% and 26% among people in the Kashmir Valley, a region with restricted economic development, political instability including elimination of semi-autonomy provisions by India in 2019, and ongoing armed conflicts ( Housen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In another study carried out among trauma victims in north central Nigeria (Dogonahawa community, Plateau state) among 266 participants, 47% being head of households and 53% being dependants. 45.2% of the head of households and 28.6% of dependents had depression (Taru et al, 2018).…”
Section: Implications Of Conflict On Mental Healthmentioning
confidence: 97%